Carbazolyl conjugate enhanced self-assembled monomolecular layer as well as preparation method and application thereof
By developing a carbazolyl conjugated self-assembled single molecule layer, the problems of poor film formation quality and high interfacial defect state density in existing perovskite solar cells are solved, and efficient hole transport and Interface optimization improves the photoelectric conversion efficiency of solar cells.
Patent Information
- Application Number
- CN202411331898.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-02-18
AI Technical Summary
In existing perovskite solar cells, the poor film formation quality of the hole transport material PTAA and the high interfacial defect state density limit the improvement of device performance and commercial applications.
Develop a carbazole-based conjugation-enhanced self-assembled single molecular layer. By carbazole as the substrate and benzene ring as the conjugated linking group, the introduction of halogen atoms can improve the interfacial function of the SAM layer and the perovskite layer, and form Dense SAM film.
It realizes efficient hole extraction and transmission, reduces the generation of interface defect states, improves the interface transmission and separation efficiency of carriers, and improves the photoelectric conversion efficiency of perovskite solar cells.
Smart Images

Figure CN119462747A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite solar cells and relates to the preparation of hole transport materials, in particular to a carbazole-based conjugated enhanced self-assembled monolayer and a preparation method and application thereof. Background Art
[0002] As a new generation of photovoltaic technology, perovskite solar cells (PSCs) have the advantages of simple preparation process, easy material adjustment, and low cost. The latest certified efficiency has reached 26.7% (National Renewable Energy Laboratory, NREL, 2024). Compared with the traditional formal structure (nip) PSCs, the inverted structure (pin) PSCs have the advantages of low-temperature processing, compatibility with large-scale manufacturing, low hysteresis, and good stability. Therefore, it has considerable development prospects in the field of perovskite photovoltaics in the future. At present, the hole transport material (HTMs) poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] (PTAA) hole transport layer commonly used in trans devices has poor wettability of perovskite solution on its surface, resulting in poor film quality and high interface defect state density. These problems limit its further performance improvement and commercial application. For this reason, the development of high-performance, new trans devices for hole transport materials is crucial to the performance of the device.
[0003] In recent years, self-assembled monolayers (SAMs) as hole transport materials have the characteristics of simple structure and flexible design. They can effectively adjust the interface energy level and reduce defect states based on molecular engineering. SAMs-type hole transport layers can be tightly bonded to the substrate through chemical bonds and have high stability. At the same time, the monolayer has a minimum layer thickness, which is also conducive to reducing parasitic absorption and improving the upper limit of device efficiency. Therefore, by developing SAMs with excellent performance through molecular engineering design, it is expected to obtain low-cost, high-efficiency HTMs and promote the commercialization of PSCs. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a carbazole-based conjugated enhanced self-assembled monolayer. The self-assembled monolayer (SAM) of the present invention uses carbazole as a substrate and a benzene ring as a conjugated linking group. It has strong hole extraction and transport properties and is a very promising hole transport material. Another purpose of the present invention is to provide a method for preparing the self-assembled monolayer, which has a simple synthesis route, good yield, and readily available raw materials.
[0005] The present invention is achieved through the following technical solutions:
[0006] A carbazole-based conjugated enhanced self-assembled monolayer, the chemical structure of which is as follows:
[0007]
[0008] Wherein, the substituent R is a methoxy group, a chlorine atom or a fluorine atom; and the substituent Ar group is a biphenyl group or a phenyl group.
[0009] A further improvement of the present invention is:
[0010] A method for preparing a carbazole-based conjugated enhanced self-assembled monolayer comprises the following steps:
[0011] S1: Compound 1 undergoes a coupling reaction with aryl halide to generate compound 2;
[0012]
[0013] S2: Compound 2 undergoes a substitution reaction with diethyl phosphite to generate compound 3;
[0014]
[0015] S3: causing compound 3 to undergo a hydrolysis reaction to generate a target product, i.e., a self-assembled monolayer material;
[0016]
[0017] The substituent R is a methoxy group, a chlorine atom or a fluorine atom; the substituent Ar group is a biphenyl group or a phenyl group.
[0018] A further improvement of the present invention is:
[0019] In S1, under argon protection, compound 1, potassium carbonate, halogenated aromatic hydrocarbon and cuprous iodide are mixed in DMAC to undergo a coupling reaction to generate compound 2, wherein the molar ratio of compound 1, halogenated aromatic hydrocarbon, potassium carbonate and cuprous iodide is 1:1-4:2-4:0.1-0.6, the reaction temperature is 100-200° C., and the reaction time is 7-12 h.
[0020] Furthermore, in S2, compound 2, palladium acetate, 1,1'-bis(diphenylphosphino)ferrocene, potassium acetate, diethyl phosphite and 1,4-dioxane are subjected to substitution reaction under an argon atmosphere to generate compound 3, wherein the molar ratio of compound 2, palladium acetate, 1,1'-bis(diphenylphosphino)ferrocene, potassium acetate and diethyl phosphite is 1:0.05-0.1:0.1-0.2:3-4:5-40, the reaction temperature is 100-200°C, and the reaction time is 10-20h.
[0021] Furthermore, in S3, compound 3 and trimethylsilyl bromide are mixed in 1,4-dioxane, and a hydrolysis reaction is carried out under an argon atmosphere, and the reaction is carried out at 25-100° C. for 10-24 hours to obtain the target product; the molar ratio of compound 3 to trimethylsilyl bromide is 1:5-10.
[0022] A further improvement of the present invention is:
[0023] The above-mentioned carbazole-based conjugated enhanced self-assembled monolayer is used in inverse perovskite solar cells.
[0024] The beneficial effects of the present invention are:
[0025] 1. The present invention provides a carbazole-based conjugated enhanced self-assembled monolayer, with carbazole as the substrate, phosphoric acid as the anchoring group, and aromatic ring as the conjugated connecting group. The conjugated aromatic ring effectively improves the planarity and conjugation degree of the SAM molecule, adjusts the work function of the ITO electrode, enhances the interaction between SAM molecules, and promotes the formation of a dense SAM film.
[0026] 2. The introduction of halogen atoms such as F and Cl promotes the interface interaction between the SAM layer and the perovskite layer, effectively passivates the surface defects of the perovskite material, improves the quality of perovskite film formation, thereby minimizing the generation of defect states at the interface and improving the interface transport and separation efficiency of carriers.
[0027] 3. When the self-assembled monolayer provided by the present invention is applied to an inverted perovskite solar cell, the short-circuit photocurrent density of the cell device reaches 25.88 mA cm -2 , the open circuit voltage is 1.171V, the fill factor (FF) is 0.8128, and the photoelectric conversion efficiency reaches 24.6%, which has practical significance for improving the efficiency of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The NMR spectrum of formula WZ-1 prepared by the present invention;
[0029] Figure 2 The NMR spectrum of formula WZ-2 prepared by the present invention;
[0030] Figure 3 The NMR spectrum of formula WZ-3 prepared by the present invention;
[0031] Figure 4 The JV curve of the inverse perovskite solar cell prepared by using the formula WZ-1 prepared by the present invention as a self-assembled monolayer;
[0032] Figure 5 The JV curve of the inverse perovskite solar cell prepared by using the formula WZ-2 prepared by the present invention as a self-assembled monolayer;
[0033] Figure 6 The JV curve of the inverse perovskite solar cell prepared by using the WZ-3 prepared in the present invention as a self-assembled monolayer. DETAILED DESCRIPTION
[0034] The present invention is described in detail below in conjunction with specific embodiments.
[0035] Example 1: Synthesis of WZ-1
[0036] This embodiment method synthesizes a carbazole-based conjugated enhanced self-assembled monolayer WZ-1, whose chemical formula is
[0037]
[0038] The specific synthetic route is as follows:
[0039]
[0040] Synthesis of compound of formula 2:
[0041] Under argon protection, raw material 1 (1.66 g, 6 mmol), 4,4'-dibromobiphenyl (2.24 g, 7 mmol), cuprous iodide (592 mg, 3 mmol), potassium carbonate (2.4 g) and DMAC (10 ml) were added to a 100 mL single-mouth round-bottom flask in sequence, and the mixed solution was heated to 180°C and refluxed for 7 h. After the reaction solution was cooled to room temperature, dichloromethane and water were added for extraction, and the organic phase was distilled under reduced pressure. The crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 50 / 1 to 10 / 1) to obtain 2.58 g of the compound shown in formula 2 as white crystals with a yield of 94%.
[0042] The structural characterization data of the compound of formula 2 are: 1 H NMR(400MHz,Chloroform-d)δ7.75(d,J=8.4Hz,2H),7.62(d,J=7.1Hz,4H),7.5 7–7.52(m,4H),7.39(d,J=8.9Hz,2H),7.06(dd,J=8.9,2.5Hz,2H),3.96(s,6H).
[0043] Synthesis of compound of formula 3:
[0044] Under argon protection, intermediate 2 (2.58 g, 5 mmol), diethyl phosphite (15.5 g, 0.1 mol), palladium acetate (63 mg, 0.25 mmol), 1,1'-bis(diphenylphosphino)ferrocene (312 mg, 0.5 mmol) and potassium acetate (1.16 g, 15 mmol) were added to a 100 mL double-necked bottle in sequence. The reaction solution was heated to 165 ° C for 18 h. After the reaction solution was cooled to room temperature, it was extracted with dichloromethane, and the excess diethyl phosphite was distilled off under reduced pressure. The crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 10 / 1 to 1 / 4) to obtain 1.8 g of intermediate 3 as a white solid with a yield of 70%.
[0045] The structural characterization data of the compound of formula 3 are: 1 H NMR (400MHz, DMSO-d6) δ8.02–7.92(m,4H),7.88–7.80(m,4H),7.72(d,J=8.6Hz,2H),7.40(d ,J=9.0Hz,2H),7.05(dd,J=8.9,2.6Hz,2H),4.06(m,1H),3.88(s,4H),1.27(t,J=7.1Hz,6H).
[0046] Synthesis of compound of formula WZ-1:
[0047] Under argon protection, intermediate 3 (1.8 g, 3 mmol), trimethylsilyl bromide (5.34 g, 30 mmol) and 10 mL 1,4-dioxane were added to a 100 mL two-necked bottle in sequence, and the mixture was reacted at room temperature for 24 h. The solvent was removed by vacuum distillation, and 5 mL methanol and 15 mL water were added to the obtained solid in sequence, and stirring was continued for 3 h. The reaction solution was filtered and washed with water to obtain a crude product. The crude product was recrystallized from methanol and water to obtain 1.28 g of a green solid with a yield of 80%.
[0048] The structural characterization data of the compound of formula WZ-1 are: 1 H NMR (400MHz, DMSO-d6) δ7.97(d,J=8.6Hz,2H),7.89–7.78(m,6H),7.70(d,J=8.5Hz,2H),7.39(d,J=8.9Hz,2H),7.05(dd,J=8.9,2.6Hz,2H),3.89(s,6H).
[0049] Example 2: Synthesis of WZ-2
[0050]
[0051] The specific synthetic route is as follows:
[0052]
[0053] Synthesis of compound of formula 2:
[0054] Under argon protection, raw material 1 (1.42 g, 6 mmol), p-chloroiodobenzene (2.55 g, 9 mmol), cuprous iodide (171 mg, 1 mmol), 18-crown ether-6 (111 mg, 0.5 mmol), potassium carbonate (3.32 g) and DMAC (10 ml) were added to a 100 mL single-mouth round-bottom flask in sequence, and the mixed solution was heated to 180°C and refluxed for 7 h. After the reaction solution was cooled to room temperature, dichloromethane and water were added for extraction, and the organic phase was distilled under reduced pressure. The crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 50 / 1 to 10 / 1) to obtain 1.5 g of the compound shown in formula 2 as white crystals with a yield of 64%.
[0055] The structural characterization data of the compound of formula 2 are: 1 H NMR (400MHz, Chloroform-d) δ8.04(d,J=2.0Hz,2H),7.75(d,J=8.6Hz,2H),7.42–7.35(m,4H),7.26(d,J=2.6Hz,2H).
[0056] Synthesis of compound of formula 3:
[0057] Under argon protection, intermediate 2 (1.5 g, 4 mmol), diethyl phosphite (10.6 g, 0.1 mol), palladium acetate (43 mg, 0.2 mmol), 1,1'-bis(diphenylphosphino)ferrocene (213 mg, 0.4 mmol) and potassium acetate (1.13 g, 12 mmol) were added to a 100 mL double-necked bottle in sequence. The reaction solution was heated to 165 ° C for 18 h. After the reaction solution was cooled to room temperature, it was extracted with ethyl acetate, and the excess diethyl phosphite was distilled off under reduced pressure. The crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 10 / 1 to 1 / 4) to obtain 1.59 g of intermediate 3 as a white solid with a yield of 92%.
[0058] The structural characterization data of the compound of formula 3 are: 1 H NMR (400MHz, Chloroform-d) δ8.11–8.01(m,4H),7.67–7.61(m,2H),7.44–7.32(m,4H),4.29–4.16(m,4H),1.40(t,J=7.1Hz,6H).
[0059] Synthesis of compound of formula WZ-2:
[0060] Under argon protection, intermediate 3 (1.58 g, 4 mmol), trimethylsilyl bromide (5.39 g, 40 mmol) and 5 mL 1,4-dioxane were added to a 100 mL two-necked bottle in sequence, and the mixture was reacted at room temperature for 24 h. The solvent was removed by vacuum distillation, and 5 mL methanol and 15 mL water were added to the obtained solid in sequence, and stirring was continued for 3 h. The reaction solution was filtered and washed with water to obtain a crude product. The crude product was recrystallized from methanol and water to obtain 1.09 g of a light pink solid product with a yield of 83%.
[0061] The structural characterization data of the compound of formula WZ-2 are: 1 H NMR (400MHz, DMSO-d6) δ8.46(d,J=1.8Hz,2H),7.97(dd,J=12.6,8.0Hz,2H),7.74(dd,J=8.3,2.8Hz,2H),7.52–7.43(m,4H).
[0062] Embodiment 3: Synthesis of WZ-3
[0063]
[0064] The specific synthetic route is as follows:
[0065]
[0066] Synthesis of compound of formula 2:
[0067] Under argon protection, raw material 1 (1.22 g, 6 mmol), p-chloroiodobenzene (2.55 g, 9 mmol), cuprous iodide (171 mg, 1 mmol), 18-crown ether-6 (111 mg, 0.4 mmol), potassium carbonate (3.32 mg) and DMAC (5 ml) were added to a 100 mL single-mouth round-bottom flask in sequence, and the mixed solution was heated to 180°C and refluxed for 7 h. After the reaction solution was cooled to room temperature, dichloromethane and water were added for extraction, and the organic phase was distilled under reduced pressure. The crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 50 / 1 to 10 / 1) to obtain 1.29 g of the compound shown in formula 2 as white crystals with a yield of 60%.
[0068] The structural characterization data of the compound of formula 2 are: 1 H NMR (400MHz, Chloroform-d) δ7.76–7.70(m,4H),7.43–7.39(m,2H),7.31–7.25(m,2H),7.17(m,2H).
[0069] Synthesis of compound of formula 3:
[0070] Under argon protection, intermediate 2 (1.29 g, 4 mmol), diethyl phosphite (9.95 g, 0.1 mol), palladium acetate (40 mg, 0.2 mmol), 1,1'-bis(diphenylphosphino)ferrocene (200 mg, 0.4 mmol) and potassium acetate (1.06 g, 12 mmol) were added to a 100 mL double-necked bottle in sequence. The reaction solution was heated to 165 ° C for 18 h. After the reaction solution was cooled to room temperature, the excess diethyl phosphite was distilled off under reduced pressure, and the crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 10 / 1 to 1 / 4) to obtain 1.32 g of intermediate 3 as a white solid with a yield of 88%.
[0071] The structural characterization data of the compound of formula 3 are: 1 H NMR (400MHz, Chloroform-d) δ8.11–7.98(m,2H),7.75–7.60(m,4H),7.38(dd,J=9.3,4.1Hz,2H),7.18(m,2H),4.23(m,4H),1.43–1.37(m,6H).
[0072] Synthesis of compound of formula WZ-3:
[0073] Under argon protection, intermediate 3 (1.32 g, 3 mmol), trimethylsilyl bromide (4.86 g, 30 mmol) and 5 mL 1,4-dioxane were added to a 100 mL two-necked bottle in sequence, and the mixture was reacted at room temperature for 24 h. The solvent was removed by vacuum distillation, and 5 mL methanol and 15 mL water were added to the obtained solid in sequence, and stirring was continued for 3 h. The reaction solution was filtered and washed with water to obtain a crude product. The crude product was then recrystallized from methanol and water to obtain 1.03 g of a light pink solid product with a yield of 90%.
[0074] The structural characterization data of the compound of formula WZ-3 are: 1 H NMR (400MHz, DMSO) δ8.16(d,J=2.7Hz,1H),8.14(d,J=2.6Hz,1H),7.95(dd,J=12.7,8.1Hz,2H),7.7 4(d,J=2.7Hz,1H),7.72(d,J=3.1Hz,1H),7.45(dd,J=9.0,4.3Hz,2H),7.32(td,J=9.1,2.7Hz,2H).
[0075] Example 4
[0076] The self-assembled monolayer WZ-1 prepared in Example 1 has a nuclear magnetic resonance spectrum as shown in Figure 1 shown.
[0077] The self-assembled monolayer WZ-1 prepared in Example 1 was used to prepare a perovskite solar cell according to the literature G. Qu; S. Cai; Y. Qiao; et al. Joule, 2024, 8, 2123-2134. The test light source was AM 1.5 (solar simulator-Oriel91160-1000, 300W), and the data was collected using a Keithley 2400 digital source meter. The test results are shown in Figure 4 The short-circuit photocurrent density of the battery device reached 25.88 mA cm -2 , the open circuit voltage is 1.171V, the fill factor (FF) is 0.8128, and the photoelectric conversion efficiency reaches 24.6%.
[0078] Example 5
[0079] The self-assembled monolayer hole transport material WZ-2 prepared in Example 1 has a nuclear magnetic resonance spectrum as shown in Figure 2 shown.
[0080] The self-assembled monolayer WZ-2 prepared in Example 2 was used to prepare a perovskite solar cell according to the literature: G. Qu; S. Cai; Y. Qiao; et al. Joule, 2024, 8, 2123-2134. The test light source: AM 1.5 (solar simulator-Oriel91160-1000, 300W), and the data was collected using a Keithley 2400 digital source meter. The test results are shown in Figure 5 The short-circuit photocurrent density of the battery device reached 25.90 mA cm -2 , the open circuit voltage is 1.167V, the fill factor (FF) is 0.8029, and the photoelectric conversion efficiency reaches 24.3%.
[0081] Example 6
[0082] The self-assembled monolayer hole transport material WZ-3 prepared in Example 1 has a nuclear magnetic resonance spectrum as shown in Figure 3 shown.
[0083] The self-assembled monolayer WZ-3 prepared in Example 3 was used to prepare a perovskite solar cell according to the literature: G. Qu; S. Cai; Y. Qiao; et al. Joule, 2024, 8, 2123-2134. The test light source: AM 1.5 (solar simulator-Oriel91160-1000, 300W), and the data was collected using a Keithley 2400 digital source meter. The test results are shown in Figure 6 The short-circuit photocurrent density of the battery device reached 25.64 mA cm -2, the open circuit voltage is 1.166V, the fill factor (FF) is 0.7811, and the photoelectric conversion efficiency reaches 23.3%.
[0084] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A carbazole-based conjugated enhanced self-assembled monolayer, characterized in that: The chemical structure is as follows: Wherein, the substituent R is a methoxy group, a chlorine atom or a fluorine atom; and the substituent Ar group is a biphenyl group or a phenyl group.
2. The method for preparing the carbazole-based conjugated enhanced self-assembled monolayer according to claim 1, characterized in that: The following steps are involved: S1: Compound 1 undergoes a coupling reaction with a halogenated aromatic hydrocarbon Ar group to generate compound 2; S2: Compound 2 undergoes a substitution reaction with diethyl phosphite to generate compound 3; S3: hydrolyzing compound 3 to generate a target product, namely, a carbazole-conjugated enhanced self-assembled monolayer; Wherein, the substituent R is a methoxy group, a chlorine atom or a fluorine atom; the substituent Ar group is a biphenyl group or a phenyl group.
3. The method for preparing a carbazole-based conjugated enhanced self-assembled monolayer according to claim 2, characterized in that: In S1, under argon protection, compound 1, potassium carbonate, halogenated aromatic hydrocarbon and cuprous iodide are mixed in N,N-dimethylacetamide to undergo a coupling reaction to generate compound 2, wherein the molar ratio of compound 1, halogenated aromatic hydrocarbon, potassium carbonate and cuprous iodide is 1:1-4:2-4:0.1-0.6, the reaction temperature is 100-200°C, and the reaction time is 7-12h.
4. The method for preparing a carbazole-based conjugated enhanced self-assembled monolayer according to claim 2, characterized in that: In S2, compound 2, palladium acetate, 1,1'-bis(diphenylphosphino)ferrocene, potassium acetate, diethyl phosphite and 1,4-dioxane are subjected to substitution reaction under an argon atmosphere to generate compound 3, wherein the molar ratio of compound 2, palladium acetate, 1,1'-bis(diphenylphosphino)ferrocene, potassium acetate and diethyl phosphite is 1:0.05-0.1:0.1-0.2:3-4:5-40, the reaction temperature is 100-200°C, and the reaction time is 10-20h.
5. The method for preparing a carbazole-based conjugated enhanced self-assembled monolayer according to claim 2, characterized in that: In S3, compound 3 and bromotrimethylsilane are mixed in 1,4-dioxane, and a hydrolysis reaction is carried out under an argon atmosphere. The reaction is carried out at 25-100° C. for 10-24 hours to obtain the target product; the molar ratio of compound 3 to bromotrimethylsilane is 1:5-10.
6. Use of a carbazole-based conjugated enhanced self-assembled monolayer as claimed in claim 1 in an inverse perovskite solar cell.
Citation Information
Cited By
N, N-bis (2-phosphonoethyl) arylamine and preparation method thereof
CN121319049A
3-hydroxy-4-(4-pyridylazo) anilino-N, N-bis (ethyl-2-phosphonic acid) and preparation method thereof
CN121362214A
Self-assembled monomolecular layer hole transport material of indeno-carbazole derivative and preparation method and application of self-assembled monomolecular layer hole transport material
CN121378339A
Self-assembled monomolecular layer hole transport material based on polycarbazole derivative and preparation method and application thereof
CN121405741A
A self-assembled monolayer hole transport material based on polycarbazole derivatives, its preparation method and application
CN121405741B